Sharing, Education and Heritage Preservation Networks: 30 years building bridges and opening paths of integration in the Americas (Cadernos de Sociomuseologia, 2020)
In regions with great social, economic, environmental and cultural inequality, such as in Latin America and the Caribbean, networking becomes critical to enhance professional development in heritage preservation aiming to value cultures, ancestors and cultural patrimony. This article presents the trajectory of APOYOnline - Association for Heritage Preservation of the Americas, a non-profit organization with more than 4,500 members, which, for the last 30 years, has been promoting professional development and especial initiatives that foster integration and cultural equity in the field of heritage preservation in Latin America, the Caribbean and other Portuguese and Spanish speaking countries. It reflects on the challenges yet to be overcome in order to achieve integral, committed and sustainable preservationKeywords: Sharing, Heritage Preservation, Education, APOYOnline, Cultural Equity